Perceived Likelihood of Developing Diabetes Among High-Risk Oregonians - Angela M. Kemple, MS; Amy I. Zlot, MPH; Richard F. Leman, MD (Centers for Disease Control and Prevention, 2005)
Introduction Prevention of diabetes in people at highest risk for developing the disease is an important public health opportunity, considering the disease's increasing prevalence, its devastating impact on health and its high economic cost, the availability of efficacious and cost-effective treatments to reduce complications, and recent evidence that it can be delayed or prevented with lifestyle interventions. Methods The Oregon Diabetes Prevention and Control Program collected and analyzed responses from a statewide telephone survey conducted in 2003 to determine whether Oregon adults at highest risk for diabetes 1) believed that they were at risk for developing diabetes in the future, 2) had talked with a health care professional about diabetes, and 3) had been tested for the disease. Pearson chi-square tests and logistic regression analyses were conducted to identify independent associations of select characteristics with the study factors of interest. Results Even among respondents at highest risk for developing diabetes, at most one third reported being concerned about developing diabetes, one fifth reported having discussed their risk with a health professional in the previous year, and less than half reported having been tested for diabetes by a health provider in the previous year. After adjusting for multiple factors, we found that having a family history of diabetes was consistently associated with perceived risk of developing diabetes, discussion about diabetes with a health professional, and diabetes testing. Conclusion Many Oregon adults at high risk for developing diabetes are unconcerned about their risk for developing the disease, and few have discussed their risk of diabetes with a health professional. Findings from this study suggest the need for increased recognition of future diabetes risk by high-risk individuals and health professionals to help translate diabetes prevention into practice.